Posible simbolismo funerario de fragmentos cerámicos en Egipto - López Grande, María José (Espacio Tiempo y Forma. Serie II, Historia Antigua, 1994)
In the spiritual life of the ancient Egyptians, the mud of the Nile as well as the water and the river's flood had an important meaning of life and regeneration. The god Jnum made the humanity in his potter-wheel with the clay of the Nile's mud, and the meaning of life and regeneration could be transfered, as a logical extensión of this belief, to soma kind of pottery vessels. Those vessels and fragments of them were used with funerary purpose, sometimes as offerings and even as fictitious coffins in modest burials.